2019
DOI: 10.1159/000502434
|View full text |Cite
|
Sign up to set email alerts
|

Updated Worldwide Epidemiology of Inherited Erythrocyte Disorders

Abstract: Introduction: Timely diagnosis and effective treatment, based on epidemiologic data, consistently reduce the clinical, social and economic burden of inherited erythrocyte disorders. Objective: This article provides an overview on current worldwide epidemiology of the most frequent inherited erythrocyte disorders. Methods: Information was obtained from Global Health Data Exchange (GHDx) database. Results: Glucose-6-phosphate dehydrogenase (G6PD) deficiency has the largest worldwide incidence and prevalence. Sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 18 publications
0
25
0
Order By: Relevance
“…If the aim is to assess the prevalence and characterize the molecular variation at the population level, genotyping is sufficient. There is a large amount of knowledge accumulated on geographical variability of G6PD (Howes et al, 2013;Bancone et al, 2019;Lippi and Mattiuzzi, 2020;Zheng et al, 2020) so that genotyping can be performed on a small panel of known mutations already described in a given population. Furthermore, full gene sequence can be used to explore rarer variants or to investigate populations lacking prior information.…”
Section: Diagnosis Of G6pd Deficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…If the aim is to assess the prevalence and characterize the molecular variation at the population level, genotyping is sufficient. There is a large amount of knowledge accumulated on geographical variability of G6PD (Howes et al, 2013;Bancone et al, 2019;Lippi and Mattiuzzi, 2020;Zheng et al, 2020) so that genotyping can be performed on a small panel of known mutations already described in a given population. Furthermore, full gene sequence can be used to explore rarer variants or to investigate populations lacking prior information.…”
Section: Diagnosis Of G6pd Deficiencymentioning
confidence: 99%
“…Secondly, different RBC conditions such as haemoglobinopathies (e.g., alpha and beta-thalassemia, haemoglobin structural variants) and membrane defects (e.g., ovalocytosis) influence the haemoglobin levels, the number of circulating reticulocytes (Bancone et al, 2017), and the intracellular oxidative state of erythrocytes (Vives Corrons et al, 1995;Margetis et al, 2007). These RBC conditions are particularly common in populations with G6PD deficiency (Lippi and Mattiuzzi, 2020). The impact of concomitant RBC conditions on the phenotypic characterisation of individuals with abnormal G6PD and on their haemolytic response to oxidative stress is not well characterised yet but might be substantial.…”
Section: Prediction Of Drug-induced Haemolysismentioning
confidence: 99%
“…In fact, countries with the highest prevalence are Africa, Asia, the Mediterranean basin and the Middle East (mean frequencies 5-25%), while in Italy it is 0-3%, with a higher prevalence among the Sardinian population (the mean frequency is 7.5%, with peaks of 25-33% in some provinces) [7]. Lippi and Mattiuzzi also reported that "the worldwide epidemiologic burden of inherited erythrocyte disorders remains particularly high" [8].…”
Section: To the Editormentioning
confidence: 99%
“…2 In the first conditional analysis, trait-specific reported variants were adjusted in the model. 3 In the second conditional analysis, all reported variants regardless of associated traits were adjusted in the model. 1 Conditional analysis at the HBA1/2 locus was performed in a subset of TOPMed samples with available alpha globin CNV data.…”
Section: Cd36 Tfrc and Slc12a7mentioning
confidence: 99%
“…RBC indices, including hemoglobin (HGB), hematocrit (HCT), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), mean corpuscular volume (MCV), RBC count, and red blood cell width (RDW), are primary indicators of RBC development, size, and hemoglobin content 2 . These routinely measured clinical laboratory assays may be altered in Mendelian genetic conditions (e.g., hemoglobinopathies such as sickle cell disease or thalassemia, red cell cytoskeletal defects, or G6PD deficiency) 3 as well as by non-genetic or nutritional factors (e.g., vitamin B and iron deficiency).…”
Section: Introductionmentioning
confidence: 99%